Bevacizumab in the treatment of HER2-negative breast cancer - Vito Lorusso (Dove Medical Press, 2008)
Vito LorussoOncologic Institute, Vito Fazzi Hospital, Lecce, ItalyAbstract: Angiogenesis has a clear and definite role in the breast cancer progression process, making antivascular endothelial growth factor (VEGF) therapies an attractive option for the treatment of metastatic breast cancer (MBC). Bevacizumab is a potent humanized monoclonal antibody to VEGF, which has shown regression of breast cancer in preclinical and clinical setting, either alone or in combination with cytotoxic treatment. Additionally, bevacizumab potentially increases the effectiveness of other anticancer therapies through the normalization of tumor vasculature, reduction of intratumoral pressure and improved tumor oxygenation. Phase 1/2 trials showed significant antitumor effects of bevacizumab in MBC, in particular in tumors not expressing HER2 receptor. A first phase 3 trial in pre-treated MBC patients showed better response rates but no survival benefit from the addition of bevacizumab to capecitabine. However, in two phase 2 trial in first-line setting in patients with MBC, bevacizumab improved progression-free survival in combination with weekly paclitaxel in comparison to paclitaxel alone or in combination with 3-weekly docetaxel in comparison with docetaxel alone, respectively. Bevacizumab in combination with taxanes seems to be a highly effective first-line treatment for MBC patients. Future research will investigate bevacizumab in the neoadjuvant or adjuvant setting, where even more potential may exist for these patients.Keywords: bevacizumab, breast cancer, HER2, HER2-negative breast cancer